Da noção epistêmica de espaço à compreensão política de lugar: uma configuração epistemopolítica em Michel Foucault - Arthur, Nilton César (2018)
Taking the basis of Michel Foucault’s historical-philosophical research, the objective is to investigate the epistemic condition of space for political understanding of place, considering, geographically and strategically, “where” bodies allocated, with positions and positioning, on a surface of socio-political contact. This is equivalent to presenting an epistemopolitical configuration. The approach emphasizes, as a methodological resource, three geometrical notions – the circle, the square and the depth – thus exposing geometrically a configuration that inevitably brings up reality, in which, more strictly, knowledge takes place in practices of power, placing a domain of know-power in socially arranged places. Thus, in the transit of juxtaposition and overlay of geometric figures, notions of circularity, framing, and depth will favor the analytical understanding of spatial dispositions in the political context, together with the intersection of historical processes. It is basing itself upon three historical periods, namely the Renaissance, the Classical Age and the Modern Age – the same privileged ones by Foucault – that the design of the epistemic space and socio-political places connected in this analysis. Thus, in the Renaissance, by the predominance of circular modulation, the outlines point the territory. In the classical period, by the predominance of the quadrangular modulation, the frameworks indicate the State. And finally, by the predominance of in-depth modulation, the structured volume points to society, with its architectures, in the Modern Age, places of vigilance, instruction, sanity, work, punishment, etc. The problematic, after all, leads to the implications between space and place, space and time or space and history. If the hypothesis that, for each historical period, there is the validation of the design of a singular space of configuration – an epistémê -, it is necessary to consider that, also in the place of surface of the practices – place both geographic and strategic -, there is the corresponding conditioning of the socio-political relations, according to the same reference and validation of the geometric metaphor